Analisis Hukum Islam terhadap Penerapan Kampung Keluarga Berencana (KB); Studi Kasus di Desa Inrello Kecamatan Keera Kabupaten Wajo - Aisyah, Siti; Sarina, Sarina (Universitas Islam Negeri Alauddin Makassar, 2020)
The author’s background raised the title of this thesis to fine out the suitability of the theory and the reality contained in the community against the implementation of the KB Village in Inrello Village Keera District Wajo Regency. The type or research method used is a qualitative research method. Qualitative research has three main keys, namely taking facts based on understanding the subject, observing in detail and in depth, and trying to find new theoretical results that are far from existing theories. Qualitative research or better known as field research starts from observation, then conducts interviews with the community, to obtain accurate data. The results showed that: 1). Lack of education is a trigger factor so that people do not understand the purpose of the implementation of the Village of KB in Inrello Village Keera District Wajo Regency. 2). KB Village Inrello Village has had a positive impact in terms of community welfare both in the economic and educational fields. 3). The implementation of the KB Village in Inrello Village is in accordance with Islamic law, where the KB Village is solely for the good and welfare of the community, it’s just that there are still many people who do not understand because they do not see the Qur,anic foundation and often ignore government programs because they maintain their opinions which is considered the most correct.Keywords: Community Understanding, KB Village, Islamic Law.